Comparison of Pain in the Kocher and Midline Incisions in Patients with Post Cholecystectomy - Yulianto, Agus; Raharjo, Agus; Alifianto, Untung; Supraptomo, RTH (Indonesian Journal of Medicine, 2020)
Background: Incision techniques that are often used in cholecystectomy laparotomy are the Kocher incision and midline incision. This study was carried out to compare the pain in the Kocher's incision and midline incision in patients with postoperative cholecystectomy laparotomy.Subjects and Method: : This study was an observational randomized controlled trial double sampling study conducted at the Department of Surgery Dr. Moewardi Hospital Surakarta in October 2018 to February 2019. The sample of this study was 30 patients aged 18-65 years old who were diagnosed with symptomatic cholelithiasis based on clinical, laboratory, and radiological tests. The samples were selected by simple random sampling. The dependent variable of this study was the pain. The independent variables were the Kocher and midline incision techniques. The pain was measured on a 24-hour postoperative VAS scale, range 1-10. Data were analyzed by t-test.Results: There was no significant difference in pain level between the Kocher group (Mean= 2.33; SD=0.72) and the midline group (Mean= 2.20; SD=0.97) with p=0.192.Conclusion: There is no difference in pain level due to the Kocher incision technique and the midline incision technique.Keywords: pain, incision, kocher, midline, cholecystectomyCorrespondence: R. Th. Supraptomo. Anesthesia dan Intensive Therapy Department Dr. Moewardi Hospital, Surakarta. Jl. Kolonel Sutarto 132 Jebres, Surakarta, Central Java 57126. Email: ekasatrio@gmail.com. Mobile: 081229229567Indonesian Journal of Medicine (2020), 05(03): 240-245https://doi.org/10.26911/theijmed.2020.05.03.09